Port Injection Of Biomass Producer Gas From Downdraft Gasifier In A Diesel Engine - Hassan, Suhaimi (2011)

(untitled)
Producer gas (PG), generated from thermo-chemical conversion process of biomass gasification has been proven to be used as an alternative fuel for internal combustion engine. However, major problems of PG when used as fuel in internal combustion engine are loss of power or engine derating and high exhaust emissions due to incomplete combustion. The most possible reasons are due to low heating value of PG itself and low energy density of PG-air mixture as compared to other alternative gaseous fuel. Based on literature studies, the main factors influencing power output from internal combustion engine fuelled with PG, particularly diesel engine are compression ratio, heating value of PG and the way of air is introduced into the engine cylinder. The method of increasing air density into engine cylinder has been selected, and the present research work deals with supercharging the diesel engine fuelled by PG under dual fuel mode with advanced fuel injection timing. Both PG from downdraft gasifier and air were compressed separately, and simultaneously injected and mixed into the engine’s cylinder via port injection. The experiments were carried out at a constant injection pressure of 200 kPa, with varying injection flow rates of both PG and air at different engine speeds and loads. The effects of fuel injection timing and supercharged on the performance, combustion characteristics and exhaust emission of single cylinder diesel engine have been experimentally investigated. Comparisons were made on diesel fuel alone, xx premixed dual fuel diesel/PG with naturally aspirated (NA) mode, premixed dual fuel diesel/PG and diesel-vegetable oil blends/PG with supercharged (SC) mode of operation. Experiments were conducted at standard 14° and advanced fuel injection timings of 17°, 20° and 23° crank angle before top dead centre. The important finding from this experiment is a major reduction of power derating that ranges between 28.12%-31.37% in a conventional premixed dual fuel D/PG with NA mode to 1.64%-6.41% in premixed dual fuel D/PG with SC mode of operations. Experimental results show that combination of using SC method and advanced fuel injection timing in dual fuel PG engine, brake thermal efficiency and diesel displacement were found increased significantly. There is a significant reduction in specific energy consumption, exhaust gas temperature, nitrogen oxides and carbon monoxide emissions. It was also observed a reduction in ignition delay and increased in cylinder peak pressure of premixed dual fuel D/PG in SC mode as compared to NA mode of operation.